Intracellular location of NR1-plasmid DNA in Escherichia coli minicells - Hochmannová, J; Nesvera, J; Stokrová, J; Perebityuk, A N (Folia microbiologica, 1981)
Intracellular location of plasmid NRI (M = 58 Mg/mol, stringent control of replication 1-2 copies per Escherichia coli chromosomal equivalent) was compared with that of plasmid R6D delta 1 (M = 21 Mg/mol, relaxed control of replication, 10-15 copies per E. coli chromosomal equivalent), both in E. coli minicells. Considerable difference in relative distribution of molecules of these two plasmid DNA's between the cytoplasm and the membrane fraction was found when components of the corresponding minicell lysates were fractionated by sedimentation in a double-linear gradient of caesium chloride and sucrose. Also the differences in relative numbers of NRI DNA and R6K delta 1 DNA molecules stably associated with the membrane of minicells, determined by electron-microscopic examination of the fractions containing plasmid DNA-membrane complexes, was evaluated as statistically significant. The association of NRI DNA molecules with E. coli minicell membrane was found to be a much more frequent event than such association of R6K delta 1 molecules. The absolute amount of plasmid DNA associated with membrane in a single minicell corresponds to one molecule for both NRI and R6K delta 1.
Keywords: Centrifugation, Density Gradient; centrifugace - gradient hustoty; DNA, Bacterial; kruhová DNA; buněčná membrána; Escherichia coli; R Factors; R-plasmidy; DNA bakterií; Cell Membrane; DNA, Circular